Analysis of Antigen‐Specific T and B Cells for Monitoring Immune Protection Against SARS‐CoV‐2. Issue 1 (4th January 2023) - De Biasi, Sara; Paolini, Annamaria; Lo Tartaro, Domenico; Gibellini, Lara; Cossarizza, Andrea
Abstract: Immunological memory is the basis of protection against most pathogens. Long‐living memory T and B cells able to respond to specific stimuli, as well as persistent antibodies in plasma and in other body fluids, are crucial for determining the efficacy of vaccination and for protecting from a second infection by a previously encountered pathogen. Antigen‐specific cells are represented at a very low frequency in the blood, and indeed, they can be considered "rare events" present in the memory T‐cell pool. Therefore, such events should be analyzed with careful attention. In the last 20 years, different methods, mostly based upon flow cytometry, have been developed to identify such rare antigen‐specific cells, and the COVID‐19 pandemic has given a dramatic impetus to characterize the immune response against the virus. In this regard, we know that the identification, enumeration, and characterization of SARS‐CoV‐2‐specific T and B cells following infection and/or vaccination require i) the use of specific peptides and adequate co‐stimuli, ii) the use of appropriate inhibitors to avoid nonspecific activation, iii) the setting of appropriate timing for stimulation, and iv) the choice of adequate markers and reagents to identify antigen‐specific cells. Optimization of these procedures allows not only determination of the magnitude of SARS‐CoV‐2‐specific responses but also a comparison of the effects of different combinations of vaccines or determination of the response provided by so‐called "hybrid immunity, " resulting from a combination of natural immunity and vaccine‐generated immunity. Here, we present two methods that are largely used to monitor the response magnitude and phenotype of SARS‐CoV‐2‐specific T and B cells by polychromatic flow cytometry, along with some tips that can be useful for the quantification of these rare events. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Identification of antigen‐specific T cells Basic Protocol 2 : Identification of antigen‐specific B cells